Bright squeezed light generation via nonclassical power stabilization - Jasper R. Venneberg; Henning Vahlbruch; Marina Trad Nery; Benno Willke (Physical Review Research)
Low-power-noise lasers are essential for many high-precision experiments. Shot noise imposes a fundamental limit on the power stability achievable with classical light sources. In this Letter, we report the generation of bright squeezed light in the audio band, which can improve the sensitivity of otherwise shot-noise-limited measurements. The bright squeezed light source is experimentally realized via the use of squeezed vacuum in a power stabilization scheme. We demonstrate a laser beam at a power of 9.9 mW with a broadband power noise suppression below the classical stabilization limit by up to 8.7_{−0.4}^{+0.3}dB in the audio band, resulting in a bright squeezed beam with a power noise of 5.7_{−0.4}^{+0.3}dB below shot noise for frequencies from 6 kHz to 20 kHz. We further conceptually outline a method to surpass this result in the future.